Antecedents of green supplier championing and greenwashing: An empirical study on leadership and ethical incentives - Blome, Constantin; Foerstl, Kai; Schleper, Martin C. (Elsevier, 2017)
Buying firms are increasingly confronted with compliance scandals in their upstream supply chain, for which they are held accountable by their stakeholders. Purely symbolic practices, typically referred to as greenwashing, as well as substantive practices, such as green supplier championing, are thus receiving widespread attention in business practices and academia alike. In this study, we reveal the impact of two opposing leadership dimensions following the concepts of ethical and transactional leadership as antecedents for green supplier championing and greenwashing. We particularly address whether these antecedents have a complementary or a counterproductive effect on green supplier championing and greenwashing. Furthermore, we investigate the complementary impact of incentives and the two leadership styles on achieving sustainability behavior. The resulting model is tested using a path analysis based on a data set of 118 firms located in Germany. We find support for the positive impact of ethical leadership on green supplier championing but also a non-significant negative impact on greenwashing. Greenwashing is significantly impacted by leadership styles reflecting obedience to authority, and further moderated by ethical incentives. Interestingly, ethical incentives do not moderate the impact of ethical leadership on green supplier championing. Finally, we discuss implications for theory and business practice.